The effects of sweet potato (Ipomoea batatas L.) extract and stevia extract on the physicochemical characteristics of effervescent granules - RACHMAT, Ridwan (2024)
This study aims to determine the effects of the ratio of sweet potato extract and stevia on the physicochemical characteristics of effervescent granules. This study uses the Factorial Randomized Group Design with three repetitions. The treatment design carried out in this study consists of one factor, namely, the comparison of sweet potato extract consisting of six levels, namely, (37.5:7.5), (35:9), (32.5:11.5), (30:14), (27.5:16.5), and (25:19). Responses in this study include chemical responses, namely, water content, pH value test, total sugar content, and anthocyanin content. Physical responses include dissolving time, hygroscopicity, color intensity, and scanning electron microscope. The comparison of sweet potato extract with stevia results showed an effect on effervescent granule characteristics, namely, total sugar content, dissolving time test, hygroscopicity level, and color intensity. This includes a moisture content of 2.56%, pH value of 3.45, total sugar content of 1.61%, and anthocyanin content of 21.19 mg/g. The best physical response results are dissolving time of 39.96 s, hygroscopicity level of 0.33%, and color intensity L* 49.46, color a* 16.55, and color b* -4.21.